(3Yed GdeQCI hCKQg Ydi OhQgG GdCSQi(B: (3egfI GdJYdje aj eOGQS WQGHdS fehPLG(B"s - (3MLGRj, RjfI GMeOs ((3HjQhJs (3GdLGeYI GddHfGfjI (B- (3eYgO GdYdhe GdGLJeGYjIs, 2013)
(3JgOa GdQSGdI Edi eYQaI GdCSHGH GdJj OaYJ GdeQCI GdYGedI aj WQGHdS Edi JaVjd egfI GdJYdje Ohf ShGgG ef Gdegf, hGdJYQa Ydi GdChVGY GdGbJUGOjI hGdfaSjI ddeQCI GdYGedI coeOqQSI, hGdChVGY GdCSQjI ef MjK GdYdGbI HGdRhL hJQHjI GdChdGO hGdGgJeGe HTDhf GdefRd(B. (3HGdEVGaI Edi GSJcTGa CKQ GdJZjQGJ GdeLJeYjI Ydi hVY GdeQCI hGdCSQI(B. (3EYJeOJ GdOQGSI Ydi GdefgL GdEMUGFj hGdefgL GdhUaj(B- (3GdJMdjdj, MjK bGe HhUa GdHjFI GdGLJeGYjI hGdCSQjI GdJj JYjT VefgG GdeYdeI, hGSJNOeJ JbfjI GdedGMXI GdHSjWI, GdGSJeGQI(B. (3TedJ GdYjfI (B130 (3eYdeI, ef (B3 (3eOGQS NGUI heOQSJjf QSejJjf aj eOjfI WQGHdS(B. (3HjfJ GdfJGFL Cf GdeQCI JaVd egfI GdJYdje Ydi ZjQgG ef Gdegf, deG ajgG ef ecGSH GbJUGOjI, agj JhaQ dgG GdQGJH GdKGHJ eeG jDef dgG GdESJbQGQ GdeGOj, cPdc JJjM egfI GdJYdje ddRhLI aQUI GdESJaGOI ef GdMSheGJ Ydi CbSGW ChdGOgG GdeOQSjI GdJj JbOegG gPg GdegfI dgG hdChdGOgG, hgPG cdg jfYcS EjLGHG Ydi faSjI GdeYdeI, hjRjOgG KbI HPGJgG, hjOaYgG ddJaGfj aj gPg GdegfI, hHGdJGdj JbOje CaVd eG YfOgG dCLjGd GdeSJbHd(B. (3ceG Cf NQhL GdeQCI Edi Shb GdYed COi Edi XghQ EjLGHjGJ YOjOI efgG EZfGA TNUjI GdeQCI HGdJLGQH hGdGgJeGeGJ hGcJSGHgG ehGbY egeI aj GdCSQI hGdYed, heeG jTLY GdeQCI CjVkG ddEbHGd Ydi GdegfI GdeMUdI GdKbGajI hGdJQHhjI, hGdejRGJ GdGLJeGYjI(B.s
(3GdfhY (B: (3QSGdIs
Keywords: La profession de l$1 (Benseignants; Teaching Career; Travail des femmes; Woman Work; (3WQGHdSs; (3Yed GdeQCIs; (3egfI GdJYdjes